Digital Tools and Decision Support Systems in Agroecology: Benefits, Challenges, and Practical Implementations - Dimitra Petraki; Ioannis Gazoulis; Metaxia Kokkini; Marios Danaskos; Panagiotis Kanatas; Andreas Rekkas; Ilias Travlos (Agronomy)
Farmers are increasingly faced with challenges such as climate change, population growth, and the need for sustainable food production, while simultaneously having to address the environmental impacts of conventional agriculture. Agroecology has emerged as a holistic and sustainable approach to agriculture, integrating environmental, social, and economic principles. This study investigates the role of digital tools, including decision support systems (DSSs), in supporting agroecological transitions. Through a literature review and analysis of case studies, this paper examines the benefits and challenges associated with the adoption of digital tools in agroecology, highlighting their potential to promote sustainable practices such as soil and water management, pest control, and efficient resource use. The findings indicate that while digital solutions offer significant potential to enhance productivity and improve environmental outcomes, their adoption remains limited due to barriers such as low digital literacy, lack of infrastructure, and concerns about effectiveness in real-world farming conditions. Despite these challenges, digital solutions offer significant potential to enhance productivity, improve environmental outcomes, and support farmers’ decision-making. To comprehensively understand their benefits, a holistic approach is necessary, combining digital tools with hands-on training, policy support, and ongoing research. This paper highlights the role of digital tools in agroecology, explores their benefits and challenges, and discusses the need for continued research to assess their long-term potential in terms of the agroecological transition.